Electrically-dismountable two-component acrylate modified polyurethane adhesive with excellent adhesive property as well as preparation method and application of electrically-dismountable two-component acrylate modified polyurethane adhesive

By introducing a specific proportion of acrylate monomers and alkali metal salts into a two-component polyurethane adhesive, combined with polyols and isocyanate prepolymers, the problems of low bonding strength and slow curing speed of existing adhesives are solved. It has the effects of fast curing speed, excellent bonding performance and electrical disassembly to meet the market demand for high-performance adhesives.

CN119351037APending Publication Date: 2025-01-24XIAMEN WELDTONE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411459631.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing electrically disassembled two-component polyurethane adhesives have problems such as low bonding strength, slow curing speed and poor reliability, which is difficult to meet the market's demand for high-performance and electrically disassembled adhesives.

Method used

By introducing a specific proportion of acrylate monomer and alkaline metal salt, combined with polyurethane pre -polystants with polyurethane compounds and isocyanate -based sealing end, prepare a dual component acrylic polyurethane adhesive to achieve fast curing speed, adhesion performance The effect of excellent and electricity disassembly.

Benefits of technology

A adhesives with fast solidification, excellent adhesion performance, and disassembly disassembly can be quickly disassembled under power -powered conditions to meet the needs of high -performance adhesives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005091501790000161
    Figure BDA0005091501790000161
Patent Text Reader

Abstract

The invention belongs to the field of two-component polyurethane adhesives, and relates to an electrically-detachable two-component acrylate modified polyurethane adhesive with excellent adhesive performance as well as a preparation method and application thereof. The two-component acrylate modified polyurethane adhesive comprises a component A and a component B which are independently stored, the component A contains a first acrylate monomer, a first alkali metal salt, a polyol compound, a small molecule chain extender, a first photoinitiator, and optionally a first silane coupling agent, a first filler, a catalyst and a first water absorbent; and the component B contains an isocyanate-terminated polyurethane prepolymer, a second acrylate monomer, a second alkali metal salt, a second photoinitiator, and an optional second silane coupling agent, a second filler and a second water absorbent. The double-component acrylate modified polyurethane adhesive provided by the invention has the advantages of high curing speed, excellent adhesive performance and electric disassembly, and is expected to meet the requirements of the market on high-performance adhesives capable of being disassembled as required.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of two-component polyurethane adhesives, and specifically relates to a two-component acrylate-modified polyurethane adhesive with excellent bonding performance and electrical disassembly, and a preparation method and application thereof. Background Art

[0002] Two-component polyurethane adhesives are usually composed of component A and component B, which can be divided into a main agent and a curing agent, wherein the main body of one component is a polyol-terminated composition, and the main body of the other component is a polyisocyanate-terminated composition. The two components are stored separately before use, and when used, the two components A and B are mixed in a certain proportion so that the polyol and the polyisocyanate undergo a nucleophilic addition reaction to achieve a curing bonding effect, thereby the two-component polyurethane adhesive can form a higher bonding strength and has excellent reliability. Due to the advantages of low construction temperature, high bonding strength, wide applicable substrates, and good reliability, two-component adhesives are widely used in many fields such as automobiles, construction, new energy batteries, and consumer electronics. However, due to the high bonding force of two-component polyurethane adhesives after curing, once poor assembly occurs or abnormal parts need to be replaced, it is often necessary to consume more manpower, material resources, and financial resources to disassemble the cured adhesive, which not only requires more costs, but also has the risk of damaging the bonding substrate. Therefore, there is an urgent need in the market for a two-component polyurethane adhesive that can be easily disassembled on demand to meet the widespread demand for adhesive removal.

[0003] In recent years, adhesives that can be disassembled under electrical conditions have received widespread attention due to the mild disassembly conditions. This is mainly achieved by adding a liquid electrolyte composed of an alkali metal salt and a solvated matrix to the adhesive, thereby making the adhesive electrically disassembleable. However, existing electrically disassembled two-component polyurethane adhesives have the defects of low bonding strength, slow curing speed, and poor reliability, and there is still a large gap compared with the traditional two-component polyurethane adhesives that are widely used. Therefore, in order to meet the market demand for high-performance, electrically disassembled two-component urethane adhesives, it is urgent to develop a two-component polyurethane adhesive that can be disassembled under electrical conditions and has excellent bonding properties. Summary of the invention

[0004] One of the purposes of the present invention is to provide a two-component acrylate modified polyurethane adhesive with fast curing speed, excellent bonding performance and electrical disassembly, in view of the shortcomings of the existing electrically disassemblyable two-component polyurethane adhesive, such as low bonding strength and slow curing speed.

[0005] Specifically, the two-component acrylate-modified polyurethane adhesive comprises independently stored component A and component B; the mass ratio of component A to component B is (1-2):1; the component A contains a first acrylate monomer, a first alkali metal salt, a polyol compound, a small molecule chain extender, a first photoinitiator and optionally a first silane coupling agent, a first filler, a catalyst and a first water absorbent; the component B contains an isocyanate-terminated polyurethane prepolymer, a second acrylate monomer, a second alkali metal salt, a second photoinitiator and optionally a second silane coupling agent, a second filler and a second water absorbent; the mass ratio of the first acrylate monomer to the first alkali metal salt is (1-8):1; the mass ratio of the first acrylate monomer to the polyol compound is 1:(1-6); the mass ratio of the second acrylate monomer to the second alkali metal salt is (1-8):1; the mass ratio of the second acrylate monomer to the isocyanate-terminated polyurethane prepolymer is 1:(1.3-6).

[0006] The second object of the present invention is to provide a method for preparing the above-mentioned two-component acrylate-modified polyurethane adhesive, which comprises: mixing a first acrylate monomer, a first alkali metal salt, a polyol compound, a small molecule chain extender, a first photoinitiator and an optional first silane coupling agent, a first filler, a catalyst and a first water absorbent to obtain a component A; mixing an isocyanate-terminated polyurethane prepolymer, a second acrylate monomer, a second alkali metal salt, a second photoinitiator and an optional second silane coupling agent, a second filler and a second water absorbent to obtain a component B; and storing the components A and B independently.

[0007] The third object of the present invention is to provide the application of the above two-component acrylate modified polyurethane adhesive in the bonding of electronic products.

[0008] After extensive and profound research, the inventors of the present invention have found that the reason for the significant decrease in the bonding reliability of the existing electrically disassembled two-component polyurethane adhesive may be that the electrically disassembled performance of the existing two-component polyurethane adhesive is mainly achieved by introducing alkali metal salts and solvation matrixes. The alkali metal salts are dissolved and separated under the action of the solvation matrix to obtain cations and anions, forming a liquid electrolyte. Under the condition of power on, the cations and anions migrate under the action of the electric field to produce a Faraday electrochemical reaction, thereby weakening the bonding strength at the adhesive interface, and realizing the function of the adhesive being electrically disassembled. However, the liquid electrolyte cannot undergo a curing reaction, and after the adhesive is cured, it still exists in the adhesive system in the initial liquid form, that is, a "plasticizer" is formed in the cured colloid, which affects the internal structure of the cured colloid, has a negative impact on the bonding strength of the adhesive, and causes a significant decrease in the bonding strength. Therefore, how to solve the problem of the presence of "plasticizers" in the cured colloid is the key to improving the bonding performance of the electrically disassembled two-component polyurethane adhesive.

[0009] The key to the present invention is to introduce specific proportions of acrylate monomers and alkali metal salts into a two-component polyurethane adhesive respectively, to prepare component A by combining a first acrylate monomer, a first alkali metal salt, a polyol compound, a small molecule chain extender, a first photoinitiator, and optionally a first silane coupling agent, a first filler, a catalyst and a first water absorbent, and to adjust the proportion of the first acrylate monomer to the polyol compound, to prepare component B by combining an isocyanate-terminated polyurethane prepolymer, a second acrylate monomer, a second alkali metal salt, a second photoinitiator, and optionally a second silane coupling agent, a second filler and a second water absorbent, and to adjust the proportion of the second acrylate monomer to the isocyanate-terminated polyurethane prepolymer, so that good interaction is exerted between the components, and the obtained two-component acrylate-modified polyurethane adhesive has fast curing speed, excellent bonding performance and can be electrically disassembled. The reason may be speculated to be that: by introducing acrylate monomers, on the one hand, alkali metal salts can be well dissolved and evenly distributed in the two-component polyurethane adhesive, giving the two-component polyurethane adhesive good electrical disassembly function; on the other hand, acrylate monomers can undergo a curing reaction by light in the presence of a photoinitiator, which not only solves the problem that the existing solvated matrix is ​​difficult to cure, but also has a faster curing speed than the traditional two-component polyurethane adhesive that relies on the nucleophilic addition reaction between the polyol and the polyisocyanate in the A and B components, thereby effectively improving the curing speed and achieving excellent bonding performance; at the same time, the ratio of the first acrylate monomer to the polyol compound and the ratio of the second acrylate monomer to the isocyanate-terminated polyurethane prepolymer are also regulated, so that the two-component acrylate-modified polyurethane adhesive can quickly establish initial bonding strength after UV curing, while maintaining a certain open time, and the UV light curing and moisture curing reaction processes occurring in the system can play a good role in mutual coordination, which is beneficial to improving the initial bonding strength. In addition, the ionic conductivity of the acrylate monomer decreases less after curing than when it is not cured, and has little effect on the ion migration ability of the cured system. It is speculated that this may be because in addition to being affected by the effect of the solvated matrix, ion migration is also related to the dipole interaction between the dissociated ions and the polymer segments. The movement of the polymer segments can help ion migration, so the acrylate monomer can still maintain good electrical disassembly performance after curing. In summary, the two-component acrylate-modified polyurethane adhesive provided by the present invention has the advantages of fast curing speed, excellent bonding performance and electrical disassembly, which is expected to meet the market demand for high-performance adhesives that can be disassembled on demand, and has broad practical application prospects. DETAILED DESCRIPTION

[0010] The two-component acrylate-modified polyurethane adhesive provided by the present invention comprises component A and component B which are stored independently. The mass ratio of component A to component B is (1-2):1, such as 1:1, 1.2:1, 1.5:1, 1.8:1, 2:1 or any value therebetween. Component A comprises a first acrylate monomer, a first alkali metal salt, a polyol compound, a small molecule chain extender, a first photoinitiator, and optionally a first silane coupling agent, a first filler, a catalyst and a first water absorbent. Component B comprises an isocyanate-terminated polyurethane prepolymer, a second acrylate monomer, a second alkali metal salt, a second photoinitiator, and optionally a second silane coupling agent, a second filler and a second water absorbent. The mass ratio of the first acrylate monomer to the first alkali metal salt is (1-8):1, such as 1:1, 2:1, 3:1, 5:1, 8:1 or any value therebetween. The mass ratio of the first acrylate monomer to the polyol compound is 1:(1-6), such as 1:1, 1:2, 1:3, 1:4, 1:5, 1:6 or any value therebetween. The mass ratio of the second acrylate monomer to the second alkali metal salt is (1-8):1, such as 1:1, 2:1, 3:1, 5:1, 8:1 or any value therebetween. The mass ratio of the second acrylate monomer to the isocyanate-terminated polyurethane prepolymer is 1:(1.3-6), such as 1:1.3, 1:1.5, 1:1.8, 1:2, 1:3, 1:4, 1:5, 1:6 or any value therebetween.

[0011] In the present invention, in component A, the content of the first acrylate monomer is preferably 10 to 30 parts by weight, such as 10, 12, 15, 18, 20, 22, 25, 28, 30 parts by weight or any value therebetween; the content of the first alkali metal salt is preferably 3 to 15 parts by weight, such as 3, 5, 8, 10, 12, 15 parts by weight or any value therebetween; the content of the polyol compound is preferably 40 to 60 parts by weight, such as 40, 42, 45, 48, 50, 52, 55, 58, 60 parts by weight or any value therebetween; the content of the small molecule chain extender is preferably 0.5 to 8 parts by weight, such as 0.5, 0.8, 1, 2, 4, 5, 6, 8 parts by weight or any value therebetween; the content of the first photoinitiator is preferably 0.5 to 10 parts by weight, such as 0.5, 0.8, 1, 2, 4, 5, 6, 8 parts by weight or any value therebetween; 5 parts by weight, such as 0.5, 0.8, 1, 2, 3, 4, 5 parts by weight or any value therebetween; the content of the first silane coupling agent is preferably 0 to 3 parts by weight, such as 0, 0.1, 0.5, 1, 1.5, 2, 2.5, 3 parts by weight or any value therebetween; the content of the first filler is 0 to 30 parts by weight, such as 0, 2.5, 5, 8, 10, 15, 20, 25, 30 parts by weight or any value therebetween; the content of the catalyst is preferably 0 to 3 parts by weight, such as 0, 0.1, 0.5, 1, 1.5, 2, 2.5, 3 parts by weight or any value therebetween; the content of the first water absorbent is preferably 0 to 3 parts by weight, such as 0, 0.1, 0.5, 1, 1.5, 2, 2.5, 3 parts by weight or any value therebetween.

[0012] In the present invention, in component B, the content of the isocyanate-terminated polyurethane prepolymer is preferably 40 to 60 parts by weight, such as 40, 42, 45, 48, 50, 52, 55, 58, 60 parts by weight or any value therebetween; the content of the second acrylate monomer is preferably 10 to 30 parts by weight, such as 10, 12, 15, 18, 20, 22, 25, 28, 30 parts by weight or any value therebetween; the content of the second alkali metal salt is preferably 3 to 15 parts by weight, such as 3, 5, 8, 10, 12, 15 parts by weight or any value therebetween; the content of the second photoinitiator is preferably 0. The content of the second silane coupling agent is preferably 0-3 parts by weight, such as 0, 0.1, 0.5, 1, 1.5, 2, 2.5, 3 parts by weight or any value therebetween; the content of the second filler is preferably 0-30 parts by weight, such as 0, 2.5, 5, 8, 10, 15, 20, 25, 30 parts by weight or any value therebetween; the content of the second water absorbent is preferably 0-3 parts by weight, such as 0, 0.1, 0.5, 1, 1.5, 2, 2.5, 3 parts by weight or any value therebetween.

[0013] In the present invention, the viscosity of the first acrylate monomer and the second acrylate monomer at 25°C is preferably 0.1 to 30 mPa.s, such as 0.1 mPa.s, 0.5 mPa.s, 1 mPa.s, 5 mPa.s, 8 mPa.s, 10 mPa.s, 15 mPa.s, 20 mPa.s, 25 mPa.s, 30 mPa.s or any value therebetween. When the viscosity of the first acrylate monomer and the second acrylate monomer at 25°C is controlled within the above preferred range, it is more conducive to the dissolution effect of the acrylate monomer on the alkali metal monomer (the first alkali metal monomer and the second alkali metal monomer), and the alkali metal monomer is better dispersed evenly in the two-component acrylate modified polyurethane adhesive system, thereby giving the two-component acrylate modified polyurethane adhesive electrical disassembly performance. The present invention does not limit the specific types and sources of the first acrylate monomer and the second acrylate monomer, and each is independently preferably selected from at least one of octadecyl acrylate, tetrahydrofuran acrylate, dodecyl acrylate, 2-phenoxyethyl acrylate, isodecyl acrylate, isooctyl acrylate, tridecyl acrylate, trimethylolpropane formal acrylate, 1,3-butanediol diacrylate, 1,4-butanediol diacrylate, diethylene glycol diacrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, tetraethylene glycol diacrylate, triethylene glycol diacrylate, tripropylene glycol diacrylate and dipropylene glycol diacrylate.

[0014] In the present invention, the first alkali metal salt and the second alkali metal salt are each independently preferably a compound composed of an alkali metal cation and at least one anion of an organic acid anion, an inorganic acid anion, and an organic sulfonyl imide anion, preferably both of which are fluorine-containing alkali metal lithium salts. The inventors of the present invention have found that when the first alkali metal salt and the second alkali metal salt are preferably each independently a fluorine-containing alkali metal lithium salt, the polyurethane adhesive can be given better power-on disassembly performance. In a preferred embodiment, the alkali metal cation of the alkali metal salt can be at least one of lithium (Li), sodium (Na), potassium (K), rubidium (Rb) and cesium (Cs), more preferably at least one of lithium (Li), sodium (Na) and potassium (K). The anion of the alkali metal salt can be at least one of trifluoromethanesulfonate ions, carboxylate ions, sulfinate ions, chloride ions, sulfate ions, sulfite ions, tetrafluoroborate ions, hexafluorophosphate ions, hexafluoroantimonate ions, nitrate ions, bistrifluoromethanesulfonyl imide ions and their substituted derivative ions. The first alkali metal salt and the second alkali metal salt are each independently preferably selected from at least one of lithium trifluoromethanesulfonate, lithium bistrifluoromethanesulfonyl imide, lithium chloride, lithium sulfate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium hexafluoroantimonate, lithium nitrate, sodium trifluoromethanesulfonate, sodium bistrifluoromethanesulfonyl imide, sodium chloride, sodium sulfate, sodium tetrafluoroborate, sodium hexafluorophosphate, sodium hexafluoroantimonate, sodium nitrate, potassium trifluoromethanesulfonate, potassium bistrifluoromethanesulfonyl imide, potassium chloride, potassium sulfate, potassium nitrate, potassium tetrafluoroborate, potassium hexafluorophosphate and potassium hexafluoroantimonate, and more preferably selected from at least one of lithium trifluoromethanesulfonate, lithium bistrifluoromethanesulfonyl imide, lithium tetrafluoroborate, lithium hexafluorophosphate and lithium hexafluoroantimonate.

[0015] In the present invention, the functionality of the polyol compound is preferably 2 to 4, such as 2, 3, 4 or any value therebetween. The number average molecular weight (Mn) of the polyol compound is preferably 200 to 3000 g / mol, such as 200 g / mol, 500 g / mol, 800 g / mol, 1000 g / mol, 1500 g / mol, 2000 g / mol, 2500 g / mol, 3000 g / mol or any value therebetween. The polyol compound is preferably at least one selected from polyether polyols, polyester polyols, castor oil polyols, polyether-modified castor oil polyols, hydroxyl-terminated liquid polybutadiene polyols, polycarbonate polyols and polyacrylate polyols.

[0016] In the present invention, the content of isocyanate groups in the isocyanate-terminated polyurethane prepolymer is preferably 5 to 25wt%, such as 5wt%, 8wt%, 10wt%, 12wt%, 15wt%, 18wt%, 20wt%, 25wt% or any value therebetween. The isocyanate-terminated polyurethane prepolymer can be commercially available or a prepolymer obtained by reacting a polyol compound with a polyisocyanate compound, and the reaction conditions can be conventionally selected in the art. Wherein, the polyol compound is preferably selected from at least one of polyether polyols, polyester polyols, castor oil polyols, polyether-modified castor oil polyols, hydroxyl-terminated liquid polybutadiene polyols, polycarbonate polyols and polyacrylate polyols. The polyisocyanate compound is preferably selected from at least one of isophorone diisocyanate, 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, diphenylmethane-4,4'-diisocyanate (MDI), hydrogenated MDI, polymeric MDI, 1,5-naphthalene diisocyanate, norbornane diisocyanate, o-toluene diisocyanate, xylylene diisocyanate (XDI), hydrogenated XDI, lysine diisocyanate, triphenylmethane triisocyanate, tris(isocyanate phenyl)thiophosphate, tetramethylxylylene diisocyanate and 1,6,10-undecane triisocyanate.

[0017] In the present invention, the small molecule chain extender is preferably selected from ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,2-propylene glycol, 1,3-butanediol, 2,3-butanediol, 2-methyl-1,3-propanediol, 1,2-pentanediol, 2,4-pentanediol, 2-methyl-1,4-butanediol, 2,2-dimethyl-1,3-propanediol, 1 , 2-hexanediol, 1,3-hexanediol, 1,4-hexanediol, 2-methyl-1,5-pentanediol, 3-methyl-1,5-pentanediol, 2-ethyl-1,4-butanediol, 1,2-octanediol, 3,6-octanediol, 2-ethyl-1,3-hexanediol, 2,2,4-trimethyl-1,3-pentanediol, 2-butyl-2-ethyl-1,3-propanediol, 2,7-dimethyl-3,6-octanediol, diethylene glycol, triethylene glycol, dipropylene glycol and tripropylene glycol.

[0018] In the present invention, the first silane coupling agent and the second silane coupling agent are each independently preferably selected from 3-mercaptopropyl trimethoxysilane, 3-mercaptopropyl triethoxysilane, 3-mercaptopropyl methyl dimethoxysilane, 3-mercaptopropyl methyl diethoxysilane, 3-glycidoxypropyl trimethoxysilane, 3-glycidoxypropyl triethoxysilane, 3-glycidoxypropyl methyl dimethoxysilane, 3-glycidoxypropyl methyl diethoxysilane, 2-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, 3-glycidoxypropyl methyl diethoxysilane, 3-aminopropyl trimethoxysilane, At least one of alkyl, 3-aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropyltrimethoxysilane, 3-(2-aminoethyl)aminopropyltriethoxysilane, 3-(2-aminoethyl)aminopropylmethyldimethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, 3-(meth)acryloxypropyltriethoxysilane, 3-(meth)acryloxypropylmethyldimethoxysilane, 3-(meth)acryloxypropylmethyldiethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane and 3-isocyanatepropyltrimethoxysilane.

[0019] In the present invention, the first photoinitiator and the second photoinitiator are each independently selected from at least one of benzophenone compounds, acetophenone compounds, acylphosphine oxide compounds, titanocene compounds, oxime ester compounds, benzoin ether compounds, and thioxanthone.

[0020] In the present invention, the first filler and the second filler are each independently selected from at least one of calcium carbonate, talc, kaolin, clay, quartz, montmorillonite, organic bentonite, hydrogenated castor oil, barium sulfate, fly ash, carbon black, fumed silica, aluminum hydroxide, magnesium hydroxide, aluminum oxide, antimony oxide, zinc borate, boron nitride, silicon carbide and melamine and its derivatives.

[0021] In the present invention, the catalyst is preferably at least one selected from dibutyltin dilaurate, stannous octoate, triethylamine, diethylenetriamine, triethylenediamine, N-ethylmorpholine and 2,2-dimorpholinyl diethyl ether.

[0022] In the present invention, the first water absorbing agent and the second water absorbing agent are each independently selected from at least one of a molecular sieve desiccant, an oxazolidine dehydrating agent, p-toluenesulfonyl isocyanate and triethyl orthoformate.

[0023] The preparation method of the two-component acrylate modified polyurethane adhesive provided by the present invention comprises: mixing a first acrylate monomer, a first alkali metal salt, a polyol compound, a small molecule chain extender, a first photoinitiator and an optional first silane coupling agent, a first filler, a catalyst and a first water absorbent to obtain a component A; mixing an isocyanate-terminated polyurethane prepolymer, a second acrylate monomer, a second alkali metal salt, a second photoinitiator and an optional second silane coupling agent, a second filler and a second water absorbent to obtain a component B; and the components A and B are stored independently.

[0024] In the preparation process of the above two-component acrylate modified polyurethane adhesive, the mixing and adding order of the raw material components can be arbitrarily combined. Preferably, the following implementation method is adopted:

[0025] For component A: S1. Stir the polyol compound, small molecule chain extender, first acrylate monomer, first alkali metal salt, first photoinitiator and optional first silane coupling agent, first water absorbent and catalyst at 100-120° C. and vacuum conditions at a speed of 100-200 r / min for 1-3 hours to obtain a premix, and transfer the premix to a mixing tank; S2. Add the first filler to the premix, place the mixing tank in a homogenizer, and mix at a speed of 1500-3000 r / min for 10-20 minutes. During the mixing, the filler on the wall of the mixing tank can be scraped into the raw material with a scraper to obtain component A;

[0026] For component B: S3. add an isocyanate-terminated polyurethane prepolymer, a second acrylate monomer, a second alkali metal salt, a second photoinitiator, and optionally a second silane coupling agent and a second water absorbent into a mixing tank, and mix them in a homogenizer at a speed of 1500-3000 r / min for 5-10 min to obtain a premix; S4. add a second filler into the above premix, and mix them in a homogenizer at a speed of 1500-3000 r / min for 10-20 min; during the mixing, the filler on the wall of the mixing tank can be scraped into the raw material with a scraper to obtain component B;

[0027] Then transfer components A and B into a two-component mixing hose and store them in a vacuum-sealed, light-proof package for later use.

[0028] The two-component acrylate modified polyurethane adhesive provided by the present invention is used in products that have a need for adhesive removal and the bonding substrate has conductivity. Specifically, the conditions for adhesive removal include: the voltage is preferably 1 to 100V, such as 1V, 3V, 5V, 7V, 9V, 10V, 20V, 50V, 60V, 80V, 100V or any value therebetween, and the power-on time is preferably 1s to 60min, 1s, 2s, 5s, 15s, 30s, 50s, 1min, 2min, 5min, 10min, 20min, 30min, 40min, 50min, 60min or any value therebetween. In addition, the bonding substrate used by the two-component acrylate modified polyurethane adhesive is a conductive substrate.

[0029] The present invention will be described in detail below through specific embodiments.

[0030] The parts involved in the following examples and comparative examples are all parts by weight.

[0031] The raw materials and sources in the following examples and comparative examples are as follows:

[0032] Castor oil polyol polycin GR-220, purchased from Vertellus, Mn = 650 mol / L, functionality 2.8; polytetramethylene ether glycol, purchased from BASF, brand PolyTHF1000, Mn = 1000 g / mol, functionality 2; castor oil polyol polycin GR-340, purchased from Vertellus, Mn = 370 mol / L, functionality 2.9; polycarbonate-1,4-butanediol-1,6-hexanediol ester glycol, purchased from Ube Industries, Ltd., Japan, brand BH-200, Mn = 2000 g / mol, functionality 2; castor oil polyol polycin GR-160, purchased from From Vertellus, Mn = 928 mol / L, functionality 2.7; polyoxypropylene ether diol, purchased from Dow Chemical Company, brand name Voranol-220-110, Mn = 1000 g / mol, functionality 2; polyethylene phthalate diol, purchased from Stepan, brand name PS-70L, Mn = 1600 mol / L, functionality 2; polyether polyol N303, purchased from Jiangsu Zhongshan Chemical Co., Ltd., Mn = 300 g / mol, functionality 3; polyhexane phthalate diol, purchased from Stepan, brand name PH-56, Mn = 2000 g / mol, functionality 2.

[0033] The p-toluenesulfonyl isocyanate water absorbent was purchased from Borchers, Germany, with the brand name Additive TI; the triethyl orthoformate water absorbent was purchased from Borchers, Germany, with the brand name Additive OF; the adsorbent molecular sieve water absorbent was purchased from Arkema, with the brand name Siliporite SA1702.

[0034] Example 1

[0035] Component A: 24.82 parts of castor oil polyol polycin GR-220, 16.22 parts of polytetramethylene glycol PolyTHF1000, 0.73 parts of butanediol, 10.00 parts of tetramethylene glycol acrylate (viscosity of 2-5 mPa.s at 25°C), 10.00 parts of diethylene glycol diacrylate (viscosity of 12 mPa.s at 25°C), 7.00 parts of lithium trifluoromethanesulfonate, 2.00 parts of photoinitiator TPO, 1.50 parts of 3-mercaptopropyltrimethoxysilane, 1.00 parts of water absorbent Additive TI and 0.50 parts of dibutyltin dilaurate were added to the reaction bottle, and stirred at a speed of 150r / min for 2h under vacuum to obtain a premix, which was transferred to a mixing tank; 26.23 parts of calcium carbonate were added to the premix, and the mixing tank was placed in a homogenizer and mixed at a speed of 2000r / min for 5min, and then the raw materials on the wall of the mixing tank were scraped into the premix with a scraper, and the mixture was mixed at a speed of 2000r / min for 5min to obtain component A;

[0036] Component B: 40.06 parts of isocyanate-terminated polyurethane prepolymer Desmodur E22, 18.17 parts of isocyanate-terminated polyurethane prepolymer Desmodur XP2762, 6.00 parts of lithium trifluoromethanesulfonate, 10.00 parts of dodecyl acrylate (viscosity at 25°C is 4-8 mPa.s), 10.00 parts of 1,6-hexanediol diacrylate (viscosity at 25°C is 5-8 mPa.s), 2.00 parts of photoinitiator 184, 2.00 parts of 3-glycidoxypropyltrimethoxysilane, 2.50 parts of water absorbent Additive TI is added to a mixing tank, and mixed in a homogenizer at a speed of 2000 r / min for 6 minutes to obtain a premix; 9.27 parts of calcium carbonate is added to the above premix, and mixed in a homogenizer at a speed of 2000 r / min for 5 minutes; then the filler on the wall of the mixing tank is scraped into the raw material with a scraper, and the mixture is continued to be mixed at a speed of 2000 r / min for 5 minutes to obtain component B;

[0037] Then, component A and component B are transferred to a two-component mixing hose to obtain a two-component acrylate modified polyurethane adhesive, which is vacuum-sealed and stored in a dark place for later use. When used, component A and component B are mixed in a weight ratio of 1:1.

[0038] Example 2

[0039] Component A: 18.50 parts of castor oil polyol polycin GR-340, 37.59 parts of polycarbonate-1,4-butanediol-1,6-hexanediol ester diol BH-200, 2.22 parts of hexanediol, 6.00 parts of isooctyl acrylate (viscosity ≤ 10mPa.s at 25°C), 6.00 parts of 1,3-butanediol diacrylate (viscosity 6mPa.s at 25°C), 4.00 parts of lithium tetrafluoroborate, 0.60 parts of photoinitiator ITX, 0.20 parts of 3-aminopropyltrimethoxysilane, 0.50 parts of water absorbent Additive OF and 0.20 parts of stannous octoate were added to the reaction bottle, stirred at a speed of 150r / min for 2h under vacuum conditions to obtain a premix, and the premix was transferred to a mixing tank; 24.19 parts of aluminum oxide were added to the above premix, the mixing tank was placed in a homogenizer, mixed at a speed of 2000r / min for 5min, and then the raw materials on the wall of the mixing tank were scraped into the premix with a scraper, and continued to mix at a speed of 2000r / min for 5min to obtain component A;

[0040] Component B: 21.05 parts of isocyanate-terminated polyurethane prepolymer Suprasec2021, 20.64 parts of isocyanate-terminated polyurethane prepolymer Desmodur XP2762, 3.00 parts of lithium tetrafluoroborate, 5.00 parts of isooctyl acrylate (viscosity ≤10mPa.s at 25°C), 5.00 parts of dipropylene glycol diacrylate (viscosity 7-13mPa.s at 25°C), 0.60 parts of photoinitiator 819, 0.10 parts of 3-acryloxypropyltrimethoxysilane, 0.20 parts of water absorbent Additive OF was added to the mixing tank, and mixed in a homogenizer at a speed of 2000 r / min for 6 minutes to obtain a premix; 24.41 parts of aluminum oxide were added to the above premix, and mixed in a homogenizer at a speed of 2000 r / min for 5 minutes; then the filler on the wall of the mixing tank was scraped into the raw material with a scraper, and the mixture was continued at a speed of 2000 r / min for 5 minutes to obtain component B;

[0041] Then, component A and component B are transferred to a two-component mixing hose to obtain a two-component acrylate modified polyurethane adhesive, which is vacuum-sealed and stored in a dark place for later use. When used, component A and component B are mixed in a weight ratio of 1.25:1.

[0042] Example 3

[0043] Component A: 24.68 parts of castor oil polyol polycin GR-160, 17.62 parts of polyoxypropylene ether glycol Voranol-220-110, 7.70 parts of 2-ethyl-1,3-hexanediol, 14.00 parts of 2-phenoxyethyl acrylate (viscosity at 25°C is 7-12mPa.s), 14.00 parts of tetraethylene glycol diacrylate (viscosity at 25°C is 10-30mPa.s), 13.00 parts of lithium hexafluorophosphate, 2.50 parts of photoinitiator 184, 1.50 parts of 3-aminopropyl triethoxysilane, 1.50 parts of water absorbent Si Liporite SA1702 and 0.60 parts of N-ethylmorpholine were added to a reaction bottle, stirred at a speed of 150 r / min for 2 hours under vacuum conditions to obtain a premix, and the premix was transferred to a mixing tank; 2.90 parts of fumed silica TS610 were added to the above premix, the mixing tank was placed in a homogenizer, mixed at a speed of 2000 r / min for 5 minutes, and then the raw materials on the wall of the mixing tank were scraped into the premix with a scraper, and continued to mix at a speed of 2000 r / min for 5 minutes to obtain component A;

[0044] Component B: 27.80 parts of isocyanate-terminated polyurethane prepolymer Desmodur E21, 22.20 parts of isocyanate-terminated polyurethane prepolymer Suprasec2444, 13.00 parts of lithium hexafluorophosphate, 15.00 parts of trimethylolpropane formal acrylate (viscosity of 12-18 mPa.s at 25°C), 10.00 parts of 1,4-butanediol diacrylate (viscosity of 2-10 mPa.s at 25°C), 3.50 parts of photoinitiator 819, 2.50 parts of vinyl trimethoxy silane, and 2.50 parts of water absorbent SiliporiteSA1702 were added to a mixing tank, and mixed at a speed of 2000 r / min for 6 minutes in a homogenizer to obtain a premix; 3.80 parts of fumed silica R202 were added to the above premix, and mixed at a speed of 2000 r / min for 5 minutes in a homogenizer; then the filler on the wall of the mixing tank was scraped into the raw material with a scraper, and the mixture was continued to be mixed at a speed of 2000 r / min for 5 minutes to obtain component B;

[0045] Then, component A and component B are transferred to a two-component mixing hose to obtain a two-component acrylate modified polyurethane adhesive, which is vacuum-sealed and stored in a dark place for later use. When used, component A and component B are mixed in a weight ratio of 1:1.

[0046] Example 4

[0047] Component A: 37.09 parts of poly(ethylene glycol phthalate) diol PS-70L, 13.91 parts of polyether polyol N303, 2.08 parts of butanediol, 8.00 parts of tridecyl acrylate (viscosity 3-11 mPa.s at 25°C), 8.00 parts of neopentyl glycol diacrylate (viscosity 10 mPa.s at 25°C), 5.00 parts of lithium bis(trifluoromethanesulfonyl imide), 2.50 parts of photoinitiator 369, 1.50 parts of 3-mercaptopropylmethyldimethoxysilane, 0.60 parts of water absorbent Additive OF and 0.70 parts of 2,2-dimorpholinyl diethyl ether were added to the reaction bottle, stirred at a speed of 150 r / min for 2 hours under vacuum conditions to obtain a premix, and the premix was transferred to a mixing tank; 20.62 parts of aluminum hydroxide were added to the above premix, the mixing tank was placed in a homogenizer, mixed at a speed of 2000 r / min for 5 minutes, and then the raw materials on the wall of the mixing tank were scraped into the premix with a scraper, and the mixture was mixed at a speed of 2000 r / min for 5 minutes to obtain component A;

[0048] Component B: 12.98 parts of isocyanate-terminated polyurethane prepolymer Desmodur E23, 33.94 parts of isocyanate-terminated polyurethane prepolymer Suprasec2021, 3.00 parts of lithium bis(trifluoromethanesulfonyl)imide, 7.00 parts of octadecyl acrylate (viscosity of 2.5 mPa.s at 25°C), 7.00 parts of triethylene glycol diacrylate (viscosity of 10-20 mPa.s at 25°C), 0.50 parts of photoinitiator 651, 0.10 parts of 3-isocyanatepropyltrimethoxysilane, 0.10 parts of water absorbent Additive OF was added to the mixing tank, and mixed in a homogenizer at a speed of 2000 r / min for 6 minutes to obtain a premix; 5.38 parts of aluminum hydroxide was added to the above premix, and mixed in a homogenizer at a speed of 2000 r / min for 5 minutes; then the filler on the wall of the mixing tank was scraped into the raw material with a scraper, and the mixture was continued to be mixed at a speed of 2000 r / min for 5 minutes to obtain component B;

[0049] Then, component A and component B are transferred to a two-component mixing hose to obtain a two-component acrylate modified polyurethane adhesive, which is vacuum-sealed and stored in a dark place for later use. When used, component A and component B are mixed in a weight ratio of 1.43:1.

[0050] Example 5

[0051] Component A: 34.31 parts of poly(hexane phthalate) glycol PH-56, 11.25 parts of castor oil polyol polycin GR-340, 2.50 parts of 2-ethyl-1,3-hexanediol, 13.00 parts of dodecyl acrylate (viscosity 4-8 mPa.s at 25°C), 10.00 parts of dipropylene glycol diacrylate (viscosity 7-13 mPa.s at 25°C), 13.00 parts of sodium trifluoromethanesulfonate, 3.40 parts of photoinitiator 1173, 2.60 parts of 3-glycidoxypropyl triethoxysilane, 2.10 parts of water absorbent Additive TI and 2.00 parts of stannous octoate were added to the reaction bottle, stirred at a speed of 150r / min for 2h under vacuum conditions to obtain a premix, and the premix was transferred to a mixing tank; 5.84 parts of talcum powder were added to the above premix, the mixing tank was placed in a homogenizer, mixed at a speed of 2000r / min for 5min, and then the raw materials on the wall of the mixing tank were scraped into the premix with a scraper, and continued to mix at a speed of 2000r / min for 5min to obtain component A;

[0052] Component B: 33.89 parts of isocyanate-terminated polyurethane prepolymer Desmodur E22, 18.04 parts of isocyanate-terminated polyurethane prepolymer Desmodur E21, 11.00 parts of sodium trifluoromethanesulfonate, 11.00 parts of 1,3-butanediol diacrylate (viscosity of 6 mPa.s at 25°C), 10.00 parts of 2-phenoxyethyl acrylate (viscosity of 7-12 mPa.s at 25°C), 2.20 parts of photoinitiator ITX, 1.60 parts of 3-glycidoxypropyltrimethoxysilane, 2.00 parts of water absorbent Additive TI was added to a mixing tank, and mixed in a homogenizer at a speed of 2000 r / min for 6 minutes to obtain a premix; 10.27 parts of talc was added to the above premix, and mixed in a homogenizer at a speed of 2000 r / min for 5 minutes; then the filler on the wall of the mixing tank was scraped into the raw material with a scraper, and the mixture was mixed at a speed of 2000 r / min for 5 minutes to obtain component B;

[0053] Then, component A and component B are transferred to a two-component mixing hose to obtain a two-component acrylate modified polyurethane adhesive, which is vacuum-sealed and stored in a dark place for later use. When used, component A and component B are mixed in a weight ratio of 1:1.

[0054] Example 6

[0055] A two-component acrylate-modified polyurethane adhesive was prepared according to the method of Example 1, except that the same number of alkoxylated nonylphenol acrylates with a viscosity of 100-160 mPa.s at 25°C were used to replace tetrahydrofuran acrylate (viscosity of 2-5 mPa.s at 25°C) and diethylene glycol diacrylate (viscosity of 12 mPa.s at 25°C) in component A and dodecyl acrylate (viscosity of 4-8 mPa.s at 25°C) and 1,6-hexanediol diacrylate (viscosity of 5-8 mPa.s at 25°C) in component B, and the other conditions were the same as those of Example 1, thereby preparing a two-component acrylate-modified polyurethane adhesive. When used, the components A and B were mixed in a weight ratio of 1:1.

[0056] Example 7

[0057] A two-component acrylate-modified polyurethane adhesive was prepared according to the method of Example 1, except that the same amount of lithium nitrate was used to replace the lithium trifluoromethanesulfonate in component A and component B, and the other conditions were the same as in Example 1, thereby preparing a two-component acrylate-modified polyurethane adhesive. When used, component A and component B were mixed in a weight ratio of 1:1.

[0058] Comparative Example 1

[0059] A reference two-component acrylate-modified polyurethane adhesive was prepared according to the method of Example 1, except that the same amount of propylene carbonate was used to replace tetrahydrofuran acrylate and diethylene glycol diacrylate in component A and dodecyl acrylate and 1,6-hexanediol diacrylate in component B, and the other conditions were the same as those of Example 1, thereby preparing a reference two-component acrylate-modified polyurethane adhesive. When used, component A and component B were mixed in a weight ratio of 1:1.

[0060] Comparative Example 2

[0061] A reference two-component acrylate-modified polyurethane adhesive was prepared according to the method of Example 1, except that lithium trifluoromethanesulfonate was not added to component A and component B, and the other conditions were the same as those of Example 1, thereby preparing a reference two-component acrylate-modified polyurethane adhesive. When used, component A and component B were mixed in a weight ratio of 1:1.

[0062] Comparative Example 3

[0063] A reference two-component acrylate-modified polyurethane adhesive was prepared according to the method of Example 1, except that no acrylate monomer was added to component A and component B, and the other conditions were the same as those of Example 1, thereby preparing a reference two-component acrylate-modified polyurethane adhesive. When used, component A and component B were mixed in a weight ratio of 1:1.

[0064] Comparative Example 4

[0065] A reference two-component acrylate-modified polyurethane adhesive was prepared according to the method of Example 1, except that the amount of acrylate monomer added in component A and component B was increased to 30 parts, and the other conditions were the same as in Example 1, thereby preparing a reference two-component acrylate-modified polyurethane adhesive. When used, component A and component B were mixed in a weight ratio of 1:1.

[0066] Test Case

[0067] The two-component polyurethane adhesives prepared in the above examples and comparative examples were tested for bonding strength, heat resistance, and high temperature and high humidity resistance before and after power-on according to the following method. The results are shown in Table 1.

[0068] (1) Bond strength at different curing times before power on: A two-component polyurethane adhesive obtained by mixing component A and component B in the embodiment and the comparative example in a certain proportion was coated on a stainless steel substrate using a dispensing machine at room temperature to form a rectangular adhesive line of 25 mm*4 mm. After coating, the adhesive was irradiated with a 365 nm UV-LED light source at 3000 mJ / cm 2 Energy, after the irradiation, another stainless steel substrate was bonded on the stainless steel substrate. After the bonding was completed, the samples were cured in an environment of 25℃ and 50%RH for 5min, 30min and 1d respectively. The prepared bonding samples were run along the shear direction at a speed of 10mm / min using a universal material testing machine until the bonding of the samples failed. The maximum force value displayed by the instrument was recorded, and the shear bonding strength of the adhesive to the stainless steel substrate after being cured for 5min, 30min and 1d was calculated based on the bonding area.

[0069] (2) Bond strength after power-on: After the glue is dispensed and cured for 1 day according to the method in (1), the sample to be tested is obtained. The positive and negative wires of the DC power supply are clamped at the two ends of the sample, respectively. The power is applied at a voltage of 48 V for 30 min or at a voltage of 60 V for 20 min. After the power-on is completed, the sample is removed and the prepared bonding sample is run along the shear direction at a speed of 10 mm / min using a universal material testing machine until the sample fails to bond. The maximum force value displayed by the instrument is recorded, and the shear bonding strength of the adhesive to the stainless steel substrate after power-on is calculated based on the bonding area (when the bonding strength is less than 2 MPa, it is removable).

[0070] (3) Heat resistance (80°C): The test samples were cured for 1 day according to the method in (1). The test samples were placed in an oven at 80°C for 20 min. The prepared bonding samples were then run in an 80°C environment at a speed of 10 mm / min along the shear direction using a universal material testing machine until the bonding failed. The maximum force value displayed by the instrument was recorded, and the shear bonding strength of the adhesive to the stainless steel substrate in a high temperature environment of 80°C was calculated based on the bonding area.

[0071] (4) High temperature and high humidity resistance: The test sample was obtained after curing for 1 day according to the method in (1). The test sample was placed in a high temperature and high humidity oven at 85°C and 85% RH for 7 days. The prepared bonding sample was run in the shear direction at a speed of 10 mm / min using a universal material testing machine until the bonding of the sample failed. The maximum force value displayed by the instrument was recorded, and the shear bonding strength of the adhesive to the stainless steel substrate after high temperature and high humidity aging was calculated based on the bonding area.

[0072] Table 1

[0073]

[0074] As can be seen from the results of Example 1 and Comparative Example 1, compared with the traditional two-component adhesive using uncurable propylene carbonate as a solvating matrix, Example 1 uses a photocurable acrylate monomer as a solvating matrix, which not only makes the bonding strength of the two-component acrylate-modified polyurethane adhesive significantly reduced after power-on, reduced to below 2MPa, and has detachability, but also has the characteristics of fast curing speed, high bonding strength, good heat resistance and high temperature and high humidity resistance. As can be seen from the results of Example 1 and Comparative Examples 2 and 3, the lack of any component in the acrylate monomer and the alkali metal salt not only reduces the bonding strength before power-on, heat resistance, and high temperature and high humidity resistance, but also the bonding strength after power-on does not decrease significantly, far higher than 2MPa, and the difficulty of disassembly is relatively large, and it does not have detachability. As can be seen from the results of Example 1 and Comparative Example 4, when the amount of acrylate added is too large, it will lead to a significant decrease in bonding performance (bonding strength before power-on, heat resistance, high temperature and high humidity resistance).

[0075] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.

Claims

1. A two-component acrylate modified polyurethane adhesive, characterized in that: The two-component acrylate-modified polyurethane adhesive comprises independently preserved component A and component B; the mass ratio of component A to component B is (1-2):1; component A contains a first acrylate monomer, a first alkali metal salt, a polyol compound, a small molecule chain extender, a first photoinitiator, and optionally a first silane coupling agent, a first filler, a catalyst and a first water absorbent; component B contains an isocyanate-terminated polyurethane prepolymer, a second acrylate monomer, a second alkali metal salt, a second photoinitiator, and optionally a second silane coupling agent, a second filler and a second water absorbent; the mass ratio of the first acrylate monomer to the first alkali metal salt is (1-8):1; the mass ratio of the first acrylate monomer to the polyol compound is 1:(1-6); the mass ratio of the second acrylate monomer to the second alkali metal salt is (1-8):1; the mass ratio of the second acrylate monomer to the isocyanate-terminated polyurethane prepolymer is 1:(1.3-6).

2. The two-component acrylate-modified polyurethane adhesive according to claim 1, characterized in that: In the component A, the content of the first acrylate monomer is 10 to 30 parts by weight, the content of the first alkali metal salt is 3 to 15 parts by weight, the content of the polyol compound is 40 to 60 parts by weight, the content of the small molecule chain extender is 0.5 to 8 parts by weight, the content of the first photoinitiator is 0.5 to 5 parts by weight, the content of the first silane coupling agent is 0 to 3 parts by weight, the content of the first filler is 0 to 30 parts by weight, the content of the catalyst is 0 to 3 parts by weight, and the content of the first water absorbent is 0 to 3 parts by weight.

3. The two-component acrylate-modified polyurethane adhesive according to claim 1, characterized in that: In the component B, the content of the isocyanate-terminated polyurethane prepolymer is 40 to 60 parts by weight, the content of the second acrylate monomer is 10 to 30 parts by weight, the content of the second alkali metal salt is 3 to 15 parts by weight, the content of the second photoinitiator is 0.5 to 5 parts by weight, the content of the second silane coupling agent is 0 to 3 parts by weight, the content of the second filler is 0 to 30 parts by weight, and the content of the second water absorbent is 0 to 3 parts by weight.

4. The two-component acrylate-modified polyurethane adhesive according to claim 1, characterized in that: The viscosity of the first acrylate monomer and the second acrylate monomer at 25° C. is independently 0.1 to 30 mPa.s; Preferably, the first acrylate monomer and the second acrylate monomer are each independently selected from at least one of octadecyl acrylate, tetrahydrofuran acrylate, dodecyl acrylate, 2-phenoxyethyl acrylate, isodecyl acrylate, isooctyl acrylate, tridecyl acrylate, trimethylolpropane formal acrylate, 1,3-butanediol diacrylate, 1,4-butanediol diacrylate, diethylene glycol diacrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, tetraethylene glycol diacrylate, triethylene glycol diacrylate, tripropylene glycol diacrylate and dipropylene glycol diacrylate.

5. The two-component acrylate-modified polyurethane adhesive according to claim 1, characterized in that: The first alkali metal salt and the second alkali metal salt are each independently a compound consisting of an alkali metal cation and at least one anion selected from the group consisting of an organic acid anion, an inorganic acid anion, and an organic sulfonyl imide anion.

6. The two-component acrylate-modified polyurethane adhesive according to claim 1, characterized in that: The first alkali metal salt and the second alkali metal salt are each independently selected from at least one of lithium trifluoromethanesulfonate, lithium bistrifluoromethanesulfonyl imide, lithium chloride, lithium sulfate, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium hexafluoroantimonate, lithium nitrate, sodium trifluoromethanesulfonate, sodium bistrifluoromethanesulfonyl imide, sodium chloride, sodium sulfate, sodium tetrafluoroborate, sodium hexafluorophosphate, sodium hexafluoroantimonate, sodium nitrate, potassium trifluoromethanesulfonate, potassium bistrifluoromethanesulfonyl imide, potassium chloride, potassium sulfate, potassium nitrate, potassium tetrafluoroborate, potassium hexafluorophosphate and potassium hexafluoroantimonate.

7. The two-component acrylate-modified polyurethane adhesive according to claim 1, characterized in that: The functionality of the polyol compound is 2 to 4; preferably, the number average molecular weight of the polyol compound is 200 to 3000 g / mol; preferably, the polyol compound is selected from at least one of polyether polyols, polyester polyols, castor oil polyols, polyether-modified castor oil polyols, hydroxyl-terminated liquid polybutadiene polyols, polycarbonate polyols and polyacrylate polyols.

8. The two-component acrylate-modified polyurethane adhesive according to claim 1, characterized in that: The content of isocyanate groups in the isocyanate-terminated polyurethane prepolymer is 5 to 25 wt %.

9. The method for preparing the two-component acrylate-modified polyurethane adhesive according to any one of claims 1 to 8, characterized in that: The method comprises: mixing a first acrylate monomer, a first alkali metal salt, a polyol compound, a small molecule chain extender, a first photoinitiator and an optional first silane coupling agent, a first filler, a catalyst and a first water absorbent to obtain a component A; mixing an isocyanate-terminated polyurethane prepolymer, a second acrylate monomer, a second alkali metal salt, a second photoinitiator and an optional second silane coupling agent, a second filler and a second water absorbent to obtain a component B; and the components A and B are stored independently.

10. Use of the two-component acrylate-modified polyurethane adhesive according to any one of claims 1 to 8 in bonding electronic products.